Glycosylation profiling of dog serum reveals differences compared to human serum. (20th August 2018) - Behrens, Anna-Janina; Duke, Rebecca M; Petralia, Laudine MC; Harvey, David J; Lehoux, Sylvain; Magnelli, Paula E; Taron, Christopher H; Foster, Jeremy M
Abstract: Glycosylation is the most common post-translational modification of serum proteins, and changes in the type and abundance of glycans in human serum have been correlated with a growing number of human diseases. While the glycosylation pattern of human serum is well studied, little is known about the profiles of other mammalian species. Here, we report detailed glycosylation profiling of canine serum by hydrophilic interaction chromatography-ultraperformance liquid chromatography (HILIC-UPLC) and mass spectrometry. The domestic dog ( Canis familiaris ) is a widely used model organism and of considerable interest for a large veterinary community. We found significant differences in the serum N- glycosylation profile of dogs compared to that of humans, such as a lower abundance of galactosylated and sialylated glycans. We also compare the N- glycan profile of canine serum to that of canine IgG – the most abundant serum glycoprotein. Our data will serve as a baseline reference for future studies when performing serum analyses of various health and disease states in dogs.